Attitudes About Consumer Strategies Among Americans in High-deductible Health Plans. Issue 3 (March 2019) - Cliff, Betsy Q.; Krenz, Christopher; West, Brady T.; Levy, Helen; Fendrick, A. Mark; Winkelman, Tyler N.A.; So, Jonathan; Fagerlin, Angela; Kullgren, Jeffrey T.
Abstract : Background: More than 70 million Americans are enrolled in a high-deductible health plan (HDHP), with high upfront cost-sharing to encourage strategies such as price shopping to mitigate out-of-pocket spending. Recent research suggests HDHP enrollees are reluctant to engage in these consumer strategies, but there is little information on why. Objectives: To describe associations between HDHP enrollees' attitudes about and intent to engage in consumer strategies. Research Design: We conducted a nationally representative web survey of 1637 HDHP enrollees that included 2 hypothetical scenarios amenable to consumer strategies. For each scenario, we asked participants whether they would compare price or quality information, discuss cost with a provider, or try to negotiate a service price. We measured participants' ratings of the difficulty of each strategy, its effectiveness at reducing cost or increasing the likelihood of getting care, and how likely participants would be to actually engage in each strategy. Results: Fewer than half of HDHP enrollees intended to engage in any of the surveyed strategies. Enrollees who viewed a consumer strategy as helpful were more likely to engage in that strategy; no associations were found with perceived difficulty of a strategy and intent to engage in it. Conclusions: HDHP enrollees may not pursue consumer strategies because they believe they are not helpful for getting care or lowering costs. Providers and payers should ensure these strategies are actually helpful to HDHP enrollees and that enrollees understand how they could use these strategies to reduce their out-of-pocket costs. Abstract : Supplemental Digital Content is available in the text.